BEAUTIFUL BORDERS. - van Ryneveld, Magda (Ancient Egypt Magazine)
The article focuses on use of painted borders and frames in ancient Egyptian two-dimensional art. Topics discussed include examples of tomb wall borders including 'Hunting in the Marshes' from the Tomb of Nakht (TT52) and the 'Son Paying Homage to his Father' scene from the Tomb of Sirenpowet II at Aswa, other examples include wooden box of Tutankhamun decorated with the 'Hunting Scene' and popularity of block-borders, history of usage of border in ancient Egypt.